The role of the international patent system in the transfer of technology to West Africa : case studies : Ghana and Nigeria - Yankey, George Sipa-Adjah (1986)
The principal aim of this thesis is to undertake a critical examination of the role of the international patent system in the transfer of technology to West Africa, particularly Ghana and Nigeria. It focuses mainly on the patent systans and technology regulatory regimes of the two countries. The study is intended to identify and evaluate the impact of the international patent system on the transfer and development of technology in this area. The first chapter provides a theoretical foundation to some of the more practical issues to be discussed in the subsequent chapters. The Paris Convention and the diplomatic revision exercise thereof, as well as other efforts and policies regarding patents and technology transfer at various levels are discussed in Chapter Two. Chapters Three to Eight consider the two case-studies undertaken in this thesis. Chapter Three begins with the historical development of the patent system in both Ghana and Nigeria, and the remaining chapters continue with a discussion of the present patent and technology regulatory regimes of both countries. Based on facts and figures the two case-studies examine critically the patent law and systems and technology transfer laws of these two countries including other related institutional measures highlighting their strengths and weaknesses. The study argues that if the patent systems of both countries are to play a meaningful role in the transfer and developnent of technology they nust be utilized as a tool of economic policy and also be related to the technology transfer regimes which nust necessarily be integrated into the national technology policy which should, in turn, be made an integral part of the entire national developnent plan. It is concluded that it is only in this way that the patent system can effectively contribute to the transfer of technology and the development of indigenous technological capabilities in the two countries.